Effects of Photobiomodulation in Sports Performance: A Literature Review - Ana González-Muñoz; Jose Javier Perez-Montilla; Maria Cuevas-Cervera; María Aguilar-García; Daniel Aguilar-Nuñez; Dina Hamed-Hamed; Leo Pruimboom; Santiago Navarro-Ledesma (Applied Sciences, 2023)
The main goal of this study is to analyze photobiomodulation therapy’s effectiveness on improving sports practice. Secondarily, the included studies were methodologically analyzed to verify their quality. A review and appraisal of literature found in Web of Science, ProQuest and Scopus databases was carried out. To evaluate the risk of bias of the included studies. The Physiotherapy Evidence Database (PEDro) scale and PEDro Internal Validity Scale (IVS) checklists were used. The included randomized clinical trials were in English, conducted on humans and published since 2016. A total of 15 randomized clinical trials were included, 4 of which found an improvement in oxygen volume after an aerobic stress test, while 2 showed no change. Muscle damage decreased in five studies, however, in two of them muscle damage did not change. Blood lactate concentration decreased in two of the studies, while in three of them there was no difference. Muscle soreness was lower in three studies, however, in four of the articles no change was demonstrated. All selected studies were of good methodological quality. On the IVS, six RCTs had a high internal quality and nine of them moderate. Photobiomodulation therapy has a positive effect on sports performance. Scientific studies on the subject are limited and more research in this line is needed.